Empowerment of Fisherman Women in the Development of Nugget Shell Business in Bluru Kidul Village, Sidoarjo District, Sidoarjo Regency - Tukiman; Rosida; S. Andarini (Future Science)
This community service is empowering women fishermen in the development of business of mussel nuggets in Bluru Kidul Village, Sidoarjo District, Sidoarjo Regency, the implementation is from March to June 2018, this community service method in the form of Training, Assistance and practice making shellfish nuggets in accordance with the recipe for dough taste, & hygiene of food products. Training, Assistance and Packaging & Labeling marketing management practices, monitoring and mentoring after training. This concept is to create a community that is independent and creative in projecting their future, families of fishermen communities in Bluru Kidul Village, Sidoarjo District, Sidoarjo Regency, will no longer depend on the local government in the development of home industry businesses in their village, but are able to stand on their own with potential in his territory. The management system based on independence and creativity in the development of the production of shellfish nuggets is still rarely found. Therefore, in the future, Bluru Kidul village is expected to become a pilot village especially in the production of shellfish nuggets in East Java in particular, and in Indonesia in general, especially for coastal villages.